Political History for the United States to Fight in Vietnam War: Failure in War Tactic of Pacification Addressing and Depicting War Tactics of Search and Destroy Using Body Count for Justifications (1935-1972) - Wadley, Kevin (My University, 2011)
In the middle of the 20th century young American men gave their lives in the jungles of Vietnam for merely political reasons decided by the politicians in Washington D.C. The War Powers Act issued after the Gulf of Tonkin by President Lyndon B. Johnson justified the reasons for American deployment in Vietnam. While American troops were in Vietnam the proper war tactics of Pacification were not correctly executed which resulted in the United States withdrawing its troops in 1972. If we had exercised our war tactics correctly rather than resorting to the war tactic of search and destroy and a war of attrition based off the idea of a victory solely depending on a body count, we would have secured another victory for America and South Vietnam would not have fallen to communism. This paper will examine the roots of the conflict, our justification for entering South Vietnam, pacification war tactics, firsthand accounts of Vietnam soldiers, and end with why search and destroy ultimately failed.
Keywords: Vietnam War, 1961-1975--Causes; Vietnam War, 1961-1975--Personal narratives, American; Vietnam War, 1961-1975--Political aspects; Strategy--Evaluation; Tactics--Evaluation